Research on the Application of UHPC in Steel-Concrete Composite Bridge Decks - Xiong, Danyang (Transactions on Engineering and Technology Research, 2024)
The high strength and toughness of ultra-high performance concrete (UHPC) show excellent performance in the steel-concrete composite bridge deck. This paper mainly discusses the application of UHPC in steel-concrete composite bridge deck. Firstly, the structural form of steel-UHPC composite bridge deck is introduced. It is emphasized that the combination of UHPC and steel plate not only reduces the dead weight of the bridge, but also improves the bearing capacity and durability of the structure. Then the mechanical properties of steel-UHPC composite bridge deck are analyzed in detail, and the advantages of UHPC in compressive strength, tensile strength and durability are emphasized. Research results have shown that the high performance of UHPC significantly improves the flexural, shear and fatigue resistance of the bridge deck, while maintaining excellent performance under harsh environmental conditions. Finally, the application of UHPC in bridge deck reinforcement is discussed, including joint reinforcement during construction and bridge deck reinforcement after construction. It is found that ultra-high performance concrete shows excellent performance in joint and bridge deck reinforcement. In summary, as a high-performance material, UHPC has a broad application prospect in steel-concrete composite bridge deck, which is helpful to solve many technical bottlenecks in traditional bridge engineering.